Simplifying calibration of bonded elasto-plastic models - Rios, S. (2016)
Using realistic constitutive models for artificially cemented soils is advantageous in design. However, the price of that increased realism is often a more elaborate model, which is difficult to calibrate. A database of high quality triaxial tests on compacted cemented silty sand is used to calibrate and validate a generalized critical state bonded soil model. The exercise highlights the staged calibration procedure that is convenient in this kind of application. The calibration results have shown a direct relation between added yield strength and a well-established soil-cement mixture ratio, which facilitates the application of the model in design. It is shown that such relation can be also deduced from the analysis of unconfined compressive strength tests.